Rapid hemostasis: a novel and effective outpatient procedure using microwave ablation to control epistaxis of isolated mucosal bulge lesions - Lou,Zheng Cai (2021)
Abstract Introduction Recurrent epistaxis is commonly encountered in the rhinology outpatient clinic. Under endoscopic guidance, both bipolar cautery and monopolar forceps (combined with suction) have been employed to control the bleeding. However, the use of monopolar forceps requires the placement of grounding pads. Most procedures are currently performed in operating rooms. Objective We investigated outcomes after the use of Microwave Ablation (MWA) to control epistaxis in adults with isolated mucosal bulge lesions. All procedures were performed with patients under local anesthesia in our outpatient clinic. Methods This is a retrospective cohort study. We included 83 adults with epistaxis of isolated mucosal bulge lesions. Microwave ablation was performed in the outpatient clinic to control bleeding, after induction of local anesthesia. The primary outcome was successful hemostasis. The secondary outcomes were the rebleeding rates at weeks 1 and 4 and month 6, and complications (crust or synechiae formation, septal perforation, and/or orbit or brain complications). Results All bleeding points were successfully ablated; hemostasis was achieved within 1-2 min. The mean pain score was 1.83 intra-operatively and 0.95 1 h postoperatively. No patient re-bled, and no severe MWA-related complication (septal perforation, synechiae formation, or orbit or brain complication) was recorded to 6 months of follow-up. Conclusions Endoscopic microwave ablation with patients under local anesthesia is a novel, safe, effective, rapid, well-tolerated, outpatient treatment for adults with epistaxis of isolated mucosal bulge lesions, especially those for whom general anesthesia might be risky, those with electrical implants, and those exhibiting contraindications for arterial embolization.